Emerging Networks : A study on learning networks during the Covid-19 lockdown - Hachmann, Roland; Kjærgaard, Thomas; Rasmussen, Hanne Fie (Proceedings of the International Conference on Networked Learning, 2024)
This paper discusses findings from an investigation of students’ experiences from and participation in different learning networks during the Covid19-lockdown. The investigation is based on empirical data in the form of 32 interviews with students from a variety of University College Programmes (business-, administration-, construction-, technology-, health-, pedagogy- and teacher education). The interviews were collected as part of a larger study, where data also consisted of responses to surveys from, potentially, 84000 students. In the interviews, the students shared their experiences regarding learning and teaching online, respectively. Three cases were singled out aiming to maintain a high degree of complexity and maximum variation. Through the contemporary theories within the field of Networked Learning, we aim to show examples of how the students were networked during the Covid-19 shutdown and the implications that emerging networks had on their participation in online educational activities. Furthermore, we wish to make a suggestion for the use of the applied categorisation of networks for analyzing how students are networked. These categories, presented in this paper, are proposed by researchers within the field. The main findings suggest that online teaching during the lockdown required students to establish new patterns of participation, thus, establishing new structures and ways to collaborate. This led to emerging networks supporting different aspects of their life setting as students and creating opportunities for engaging in new social configurations and learning.